Sustainable Business Marketing - Dan-Cristian Dabija (Amfiteatru Economic)
The evolution of the business world in harmony with the principles of sustainability has been increasingly significant in our century. Displaying a planned, integrated and properly coordinated entrepreneurial orientation toward environment protection, the involvement in the actions initiated by the local community and by society in general or supporting and streamlining one’s own economic activity on a lasting basis represent key elements whereby a business can achieve harmonious increase in time, a synergic evolution and even competitive advantage. There is, however, a major problem, namely, the sustainable development directions and principles are difficult to understand and, in particular, to apply to entrepreneurial decisions and marketing strategies so as to ensure the investment and financial capital to support the organization’s activities and identify the consumers willing to pay the price of sustainability. It is impossible to define objectives capable of meeting such requirements and successfully implement strategies ensuring a healthy growth and constant development without referring to the sustainability of the actions made and their impact on the environment, human society, the company’s employees and the effectiveness of the activity conducted. In this issue, the Amfiteatru Economic journal hosts a number of original studies which contribute to the application of the concept of sustainable marketing and its facets to different economic sectors from a business marketing point of view. The research made by the authors is both transnational and transdisciplinary, capturing in a harmonious way the various facets of sustainable business marketing.